Extramedullary Leukemia, Presenting at the Cervix of the Uterus - Nikolaos Tsagkas; Androniki Troussa; George Vorgias; Olympia Tzaida; Nektaria Zagorianakou; Maria Gonidi (Hindawi Limited, 2020)
Extramedullary relapse of leukemia is encountered more often than in the past. The reason is that leukemia survival rates increase with improved treatment schemes. We present a rare case of involvement of the cervix of the uterus in an adult B Acute Lymphocytic Leukemia (B-ALL) survivor. Relapses affect various organs but rarely the female genital tract. Nevertheless, in this case, a woman with a history of induced amenorrhea due to treatment for leukemia presented to the gynecologist because of vaginal spotting. Colposcopy evaluation of the vagina/cervix, sonography and cytological and histological sampling established the diagnosis of leukemia relapse in the cervix of the uterus. Under these circumstances, our study highlights the rare extramedullary presentation of leukemia in the cervix of the uterus of a young lady considered to be disease-free and listed for bone marrow transplantation. In this rare case of relapse in the cervix of the uterus, Pap smears alarmed physicians, and radiology examinations assisted the diagnostic workup. Still, only biopsy, microscopic evaluation, and immunohistochemistry studies established the exact diagnosis. Prognosis in the situation of extramedullary disease relapse in the female genital tract was poor, but gynecologists' high suspicion led to a prompt diagnosis. Survival is in general limited, but together with high suspicion, multidisciplinary team involvement is imperative to improve the reduced chances of survival.